PENGARUH INFLASI, SUKU BUNGA, DAN NILAI TUKAR RUPIAH TERHADAP HARGA SAHAM INFOBANK15 (PERIODE 2018 – 2022) - Yuanitasari, Annastasia Anisah; Sri Nawatmi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
Stock market can be fluctuate and uncontrolled depends on many internal and external factors. The fluctuation itself can bring impact to capital market entities and the economy. This study focused for investigate the effects of inflation, interest rate, and domestic exchange rate on INFOBANK15 price stock during the 2018 – 2022 periods. This study collects data from Indonesia Stock Exchange which can be downloaded from idx.co.id. A quantitative approach to analyze the data and using SPSS as the tools. The result indicate that inflation has no effect to price stock, interest rate and exchange rates gives negative effect to stock prices.